Fostering Social Interdependence: Management of Coop-erative Learning in Arts and Crafts to Enhance Collabo-rative Skills in Indonesian Elementary Schools - Kuntari, Ari Kukuh; Abdurrahman , Nana Herdiana (CV. Media Digital Publikasi Indonesia, 2026)
In the landscape of 21st-century education, the cultivation of collaborative skills is as critical as cognitive development. This study investigates the effectiveness of learning management within Arts and Culture and Crafts (SBdP) based on cooperative group strategies at SDN Dewi Sartika and SDN Sindangsari. Utilizing a qualitative descriptive approach within a Classroom Action Research framework, data were harvested through participant observation, in-depth interviews, and structured rubric assessments. The study reveals that a systematic management approach—encompassing strategic planning, heterogeneous organization, multimodal execution, and holistic evaluation—significantly enhances students' communication, empathy, and collective responsibility. The findings indicate that when Arts education is managed through the lens of social interdependence theory, it transcends aesthetic creation to become a medium for character building. The research concludes that structured group learning management acts as a scaffold for social competence, aligning with national character education goals. These insights offer a pedagogical blueprint for educators seeking to integrate soft skills development within creative subjects.